Impact of helicopter emergency medical services in major incidents: systematic literature review - Johnsen, Anne Siri (BMJ Publishing Group, 2013)
INTRODUCTION: Helicopter emergency medical services (HEMS) aim to bring highly specialised crews to the major incident for triage, treatment and transport. When the site is difficult to access, HEMS may be the only mode of transportation of both personnel and patients. This systematic review will identify, describe and appraise literature regarding the role of HEMS in medical response to major incidents. We aim to improve knowledge on HEMS role in a major incident and provide a basis for future research. METHODS AND ANALYSIS: A systematic literature review will be conducted with search phrases that combine HEMS and major incidents to identify when and how HEMS have been used. Included literature will be subject to quality appraisal and data extraction. ETHICS: No ethical approval is sought because this is a literature review. It will be submitted to a peer-reviewed journal and the PRISMA guidelines will be followed. REGISTRATION DETAILS: PROSPERO CRD42013004473